2018
DOI: 10.1177/0192623318803557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diet-induced Obesity on Toxicological Parameters in the Polygenic Sprague-Dawley Rat Model

Abstract: The obese rodent serves as an indispensable tool for proof-of-concept efficacy and mode-of-action pharmacology studies. Yet the utility of this disease model as an adjunct to the conventional healthy animal in the nonclinical safety evaluation of anti-obesity pharmacotherapies has not been elucidated. Regulatory authorities have recommended employing disease models in toxicology studies when necessary. Our study investigated standard and exploratory toxicology parameters in the high-fat diet (HFD)-induced obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 117 publications
1
8
0
1
Order By: Relevance
“…Long-term HFD studies showed a significant decrease in haematological parameters [54,55]. This study observed a slight decline in the value of Hb, RBC, MCH and a significant decrease in HCT and MCV in HFD fed mice.…”
Section: Discussionsupporting
confidence: 50%
“…Long-term HFD studies showed a significant decrease in haematological parameters [54,55]. This study observed a slight decline in the value of Hb, RBC, MCH and a significant decrease in HCT and MCV in HFD fed mice.…”
Section: Discussionsupporting
confidence: 50%
“…Both strains can manifest the many characteristics of MetS with no serious inconsistencies or conflicts. SD rats and SHR have been established by decades of research and are considered useful models of DIO [ 47 , 48 , 49 ]. However, the Wistar rat model has a recurring issue.…”
Section: Resultsmentioning
confidence: 99%
“…Data from Tekus et al (2018) provide reference values of body fat percentage of rats at various ages up to two years. While the study used only male Wistar (rather than Sprague Dawley) rats, other studies indicate that body fat percentage is similar across the two strains ( Reed et al, 2011 ) and between male and female Sprague Dawley rats ( Rojas et al, 2018 ). Fig.…”
Section: Resultsmentioning
confidence: 99%